Molecularly Imprinted Nanoparticle Ensembles for Rapidly Identifying S. epidermidis - Chularat Hlaoperm; Wisnu Arfian A. Sudjarwo; Jakob Ehrenbrandtner; Endre Kiss; Giorgia Del Favero; Kiattawee Choowongkomon; Jatuporn Rattanasrisomporn; Peter A. Lieberzeit (Sensors, 2023)
Staphylococcus epidermidis (S. epidermidis) belongs to methicillin-resistant bacteria strains that cause severe disease in humans. Herein, molecularly imprinted polymer (MIP) nanoparticles resulting from solid-phase synthesis on entire cells were employed as a sensing material to identify the species. MIP nanoparticles revealed spherical shapes with diameters of approximately 70 nm to 200 nm in scanning electron microscopy (SEM), which atomic force microscopy (AFM) confirmed. The interaction between nanoparticles and bacteria was assessed using height image analysis in AFM. Selective binding between MIP nanoparticles and S. epidermidis leads to uneven surfaces on bacteria. The surface roughness of S. epidermidis cells was increased to approximately 6.3 ± 1.2 nm after binding to MIP nanoparticles from around 1 nm in the case of native cells. This binding behavior is selective: when exposing Escherichia coli and Bacillus subtilis to the same MIP nanoparticle solutions, one cannot observe binding. Fluorescence microscopy confirms both sensitivity and selectivity. Hence, the developed MIP nanoparticles are a promising approach to identify (pathogenic) bacteria species.